1987
DOI: 10.1093/infdis/155.5.979
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Berberine Sulfate Therapy for Diarrhea Due to Enterotoxigenic Escherichia coli and Vibrio cholerae

Abstract: To evaluate the antisecretory activity of berberine sulfate (BS), we studied 165 adult patients with acute diarrhea due to enterotoxigenic Escherichia coli (ETEC) and Vibrio cholerae in randomized controlled trials. In patients with ETEC diarrhea who received 400 mg of BS in a single oral dose, the mean stool volumes were significantly less than those of the controls during three consecutive 8-hr periods after treatment (P less than .05). At 24 hr after treatment, significantly more patients who were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(115 citation statements)
references
References 23 publications
1
114
0
Order By: Relevance
“…It also exhibits antitumor, antimicrobial, and even antidiabetic effects (31)(32)(33)(34)(35)(36). Moreover, a recent report suggested that BBR may be efficacious in experimental type I diabetes (37), raising the possibility of its use as a treatment for autoimmune diseases.…”
mentioning
confidence: 99%
“…It also exhibits antitumor, antimicrobial, and even antidiabetic effects (31)(32)(33)(34)(35)(36). Moreover, a recent report suggested that BBR may be efficacious in experimental type I diabetes (37), raising the possibility of its use as a treatment for autoimmune diseases.…”
mentioning
confidence: 99%
“…Ϫ was less sensitive than BLS303 to the third compound, the phytoalexin berberine, an alkaloid found in herbs such as berberis and goldenseal (46). The fourth compound, the phytoalexin cafestol, is a diterpene isolated from the bean of Coffea arabica (47).…”
Section: Requirement Of Wxocb For the Lps O Chain And For Normal Accumentioning
confidence: 98%
“…It is traditionally used in China to treat gastrointestinal diseases such as dysentery and diarrhea. Clinical studies conducted in 1985 and 1987 have shown that berberine is considered to be a non-toxic alkaloid and is useful for the treatment of bacterial diarrhea (136,242). Berberine also has anti-fungal (76), anti-human immunodeficiency virus (HIV) infection (53), and anti-protozoan properties (131).…”
Section: The Inhibitory Mechanisms Of Natural Compounds Against Npc Smentioning
confidence: 99%